PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR KESEHATAN DI BURSA EFEK INDONESIA - Michael Ivan Christianto (2022)
This study was conducted to determine and analyze the effect of firm size, profitability and liquidity on firm value. The population used in this study is the health sector companies listed on the Indonesia Stock Exchange (IDX). This study used purposive sampling and obtained 14 companies in the health sector with a period of six years of research and obtained 84 samples. The data analysis technique used is Panel Data Regression Analysis using the Eviews 12 program with a significance level of 5%. This study shows that firm size as measured by SIZE has a negative effect on firm value, profitability measured by return on assets (ROA) has a positive and significant effect on firm value, liquidity as measured by the current ratio has no effect on firm value.